Peer Instruction in a Flipped Learning Environment: Investigating ESL Students’ Critical Thinking Performance in Argumentative Essay Writing - Amreet Kaur Jageer Singh; Raja Nor Safinas Raja Harun (Universitas Sulawesi Barat, 2021)
Research shows that peer instruction and flipped learning help ESL/EFL students compensate for their shortcomings in their language, support the language learning process, and facilitate social interactions and collaboration between teachers and students in the class. Despite this, there has been little research into whether upper-intermediate ESL students can benefit from the use of peer instruction in a flipped learning environment in enhancing critical thinking performance in argumentative essay writing. This current study tests this hypothesis. A total of 120 English Proficiency 4 (EP4) students from a teacher education university in Malaysia were equally divided into two experimental groups (pair work and group work) and a control group (conventional teaching method). The experimental groups’ activities included a focus on different modes of peer instruction (pair work/group work) and flipped learning, while the control group’s did not. Two research instruments were employed in this study: pre- and post-tests and a holistic scoring rubric. The critical thinking aspect was adapted from Stapleton and Wu (2015) and Toulmin’s model of argumentation (2003). Descriptive and inferential statistics, namely, one-way analysis of variance (ANOVA) was computed using IBM SPSS Statistics 26. Overall, compared to the control group, both experimental groups (pair work and group work) performed better in mean scores for critical thinking in the posttest. The result of the study suggests that the use of peer instruction in a flipped learning environment can be an alternative teaching method to enhance the students’ critical thinking in argumentative essay writing and offer implications for ESL students, language instructors, and researchers.